New and rare Schizomida (Arachnida: Hubbardiidae) from South America - Cokendolpher, J. C.; Reddell, J. R. (Amazoniana, 2000)
One new genus and eight new species of Schizomida are described from South America: Adisomus duckei n.g., n.sp. from Brazil, Rowlandius sul n.sp. from Brazil, Surazomus arboreus n.sp. from Brazil, S. manaus n.sp. from Brazil, S. mirim n.sp. from Brazil, and S. rodriguesi n.sp. from Brazil; Hansenochrus guyanensis n.sp. from Guyana; and Surazomus boliviensis n.sp. from Bolivia. New records of Surazomus brasiliensis (KRAUS) are included and the female genitalia are illustrated.
Keywords: Schizomida